Effect of Mulligan’s mobilization with movement and eccentric exercises for lateral epicondylitis in recreational tennis players - Manandhar, Ronit; Haridass, Sarulatha (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Recreational tennis players often have been documented to suffer from lateral epicondylitis (LE). There is a lack of evidence on the effects of Mulligan’s mobilization with movement (MWM) and eccentric exercises in recreational tennis players with lateral epicondylitis. Aim of Study. To find the effect of Mulligan’s MWM along with eccentric exercise on grip strength and functional disability in recreational tennis players for lateral epicondylitis. Material and Methods. Thirty subjects based on the inclusion criteria were recruited through referrals. The experimental group underwent Mulligan’s MWM along with eccentric exercise and the control group intervention comprised solely of eccentric exercise program 3 sessions a week for 4 weeks. Grip strength using Hand Held Dynamometer and functional abilities using Patient Rated Tennis Elbow Evaluation (PRTEE) were measured. Data were analyzed using SPSS 16.0 with descriptive and inferential statistics at 5% level of significance. Results. Analysis demonstrated statistically significant improvements for both outcomes in both the experimental group and the control group. Improvements for both dependent variables were greater for the experimental group. Conclusions. The administration of Mulligan’s MWM along with eccentric exercise was found to be more effective than eccentric exercise alone to increase grip strength and functional abilities in recreational tennis players with lateral epicondylitis.
Keywords: lateral epicondylitis; mobilization; eccentric; mulligan; recreational tennis